Older adults’ perceptions and experiences of online social support - Pfeil, Ulrike; Zaphiris, Panayiotis; Wilson, Stephanie (My University, 2009)
This paper reports an investigation of older adults’ needs and preferences concerning online social support. We focused our analysis on seven different aspects of online support: Self disclosure, Deep support, Light support, Community building, Information/Facts, Off topic, and Technical issues. For each aspect we were interested in how older adults perceive this aspect of support, what they think are the similarities and differences of this aspect of support in online settings vs offline settings, and what they perceive are the advantages and disadvantages of communicating this aspect of support online. We did this by conducting detailed interviews with three groups of older adults (31 people in total) with different levels of expertise in using the internet and online communication (older adults who do not use the internet, older adults who use only email, and older adults who participate in online support communities). Interviews were transcribed verbatim and analyzed. Our findings describe older adults’ perception of different aspects of support and identify their motivation for turning to online support and the reasons for any reluctance to do so. Thus, our findings give insight into how online support communities could best be utilized to improve older people’s experience with online support.
Keywords: Older people; Online communities; CMC